Revisiting the conformational adsorption of L‐ and D‐cysteine on Au nanoparticles by Raman spectroscopy. (18th December 2019) - Rodríguez‐Zamora, P.; Salazar‐Angeles, B.; Buendía, F.; Cordero‐Silis, C.; Fabila, J.; Bazán‐Díaz, L.; Fernández‐Díaz, L.M.; Paz‐Borbón, L.O.; Díaz, G.; Garzón, I.L.
Abstract: Understanding the physical mechanisms of thiolated molecules adsorption on metal surfaces has required copious research, particularly on Au–cysteine systems due to the affinity of sulfur molecules to gold surfaces, as well as the interesting structural modifications that this strong interaction induces and the peculiar optical, chiroptical, and electronic properties of Au(SR) systems. Here, we present vibrational experimental data on the adsorption of L ‐ and D ‐cysteine on small gold nanoparticles (<2 nm) by means of Raman spectroscopy. L ‐ and D ‐cysteine molecules adopt the same strained conformation upon adsorption on colloidal gold nanoparticles, regaining structure due to the stabilization that the gold nanoparticle induces on the cysteine, reflected in the recuperation of vibrational bands from their polymorphically distinctive crystalline forms. Through the analysis of Raman vibrational modifications after adsorption, we found experimental evidence that confirms a stabilized cysteine conformation locating the carboxyl group in the antiposition (P C isomeric rotamer) for both molecules. This result is supported by extensive density functional theory (DFT) calculations and simulated Raman spectra, considering zwitterionic cysteine adsorbed on a Au34 cluster, emulating experimental nanoparticle sizes. Our Raman spectroscopy experimental and DFT results determine one of the oxygen atoms of the carboxyl group as a second adsorption site after the sulfur atom, confirming that independent of its polymorphism and enantiomerism, zwitterionic cysteine interacts with gold nanoparticles through the thiol group and the carboxyl group as adsorption sites. Abstract : Experimental vibrational data of small (>2 nm) synthesized L ‐ and D ‐cysteine capped gold nanoparticles are obtained by means of Raman spectroscopy, confirming a stable conformation for cysteine that locates the carboxyl group in the antiposition for both L ‐ and D ‐cysteines. Au34 Cys configurations are obtained using DFT‐D3 global optimization random searches in order to explore the preferred cysteine adsorption sites and calculate the Raman spectra. General analysis confirms the cysteine interaction with gold through the carboxyl and thiol groups.